Front Cover: Investigating Protein–Ligand Interactions by Solution Nuclear Magnetic Resonance Spectroscopy (ChemPhysChem 8/2018). Issue 8 (16th April 2018) - Becker, Walter; Bhattiprolu, Krishna Chaitanya; Gubensäk, Nina; Zangger, Klaus
Abstract : The Front Cover symbolizes the two‐pronged approach to obtain information about protein–ligand interactions by solution NMR. It shows the structure of the rapamycin–FKBP complex with the corresponding protein and ligand spectra in the setting of our local NMR lab. More information can be found in the Review by W. Becker et al. onpage 895 in Issue 8, 2018 (DOI:10.1002/cphc.201701253 ).